The functions of the Hsp70 system - Brodsky, Jeffrey L. (Henry Stewart Talks, 2007)
Early steps and problems in nascent protein folding, Molecular chaperones prevent protein aggregation, Heat shock protein (molecular chaperone) classes, Hsp70: characteristics and mechanism of action, Hsp70 function and cancer (prevention of apoptosis), Hsp70 function and viral replication (the polyomaviruses), Hsp70 function and protein conformational diseases (ERAD), Update interview: Hsp70 and cellular protein homeostasis (“proteostasis”), Update interview: Hsp70: a molecular machine, Update interview: Hsp70: a validated target in some cancers
Updated at 2020/05/16